(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
تعمل وزارة التربية على الاستفادة من التطورات الحاصلة في المجال التقاني من خلال توظيفها في العملية التربوية بما يسهم في تطويرها. فكان إطلاق القناة الفضائية التربوية السورية خطوة نحو مجتمع المعرفة والاستفادة من التقنيات الحديثة، وذلك من خلال تقديمها لمجموعة من البرامج المتنوعة ذات المضمون الثقافي والتربوي والعلمي، والدروس التعليمية المتماشية مع المناهج المعتمدة في المراحل التعليمية المختلفة. لذا هدف البحث إلى معرفة درجة إفادة طلبة الشهادة الثانوية العامة في مدارس محافظة ريف دمشق من الدروس التعليمية المعروضة على القناة الفضائية السورية التربوية، والكشف عما إذا كانت هناك فروق ذات دلالة إحصائية بينهم تبعاً لمتغيرات البحث (الجنس، الاختصاص). أجري هذا البحث على عينة من طلبة الشهادة الثانوية العامة في مدارس محافظة ريف دمشق للعام الدراسي2011-2012 والتي بلغت(84)طالباً وطالبة. استخدم الباحث في دراسته استبانة مؤلفة من (16) عبارة. وتوصل الباحث إلى نتائج أهمها: 1ـ يستفيد طلبة الشهادة الثانوية العامة بدرجة متوسطة من الدروس التعليمية المعروضة على الفضائية التربوية السورية. 2.لا توجد فروق ذات دلالة إحصائية في درجة إفادة طلبة الشهادة الثانوية العامة من الدروس المعروضة على الفضائية التربوية السورية تبعاً لمتغير الجنس، بينما توجد فروق بينهم تبعاً لمتغير الاختصاص. 3. من أهم أسباب عدم متابعة بعض التلاميذ لدروس القناة ضخامة المنهاج، انقطاع التيار الكهربائي. على أثر النتائج التي توصل إليها الباحث انتهى إلى وضع التوصيات: 1ـ الدعوة إلى التنسيق بين قطاع التربية وقطاع الإعلام بما يخدم العملية التعليمية. 2 ـ إقامة دورات تدريبية للمعلمين لرفع كفاءتهم فيما يتعلق بتعاملهم مع الأجهزة التعليمية. 3. الاهتمام بشكل أكبر بتوفير قاعات مهيأة لاستقبال البث التلفزيوني للدرس. The Ministry of Education, in Syria, is working to take advantage of developments in the field of technology by employing them in the educational process so as to contribute to its development. So, the launch of the Syrian educational satellite channel was a step towards a knowledgable society and the use of modern technologies, and through the submission of a group of diverse programs with cultural content, educational and scientific, and educational lessons that are consistent with the approved curriculum in the various stages of education. The goal of the research is to find out the degree to benefit GCSE students in schools in the province of Damascus Countryside of tutorials offered on the Syrian Educational Satellite Channel, and detect whether there were statistically significant differences between them depending on the research variables (sex, jurisdiction). This research was conducted on a sample of GCSE students in schools in the province of Damascus for the 2011-2012 academic year, which amounted to (84) students. The researcher used a questionnaire consisting of (16) phrase. The researcher has found that: 1 there is a medium degree of benefit for GCSE students of tutorials offered on the Syrian educational channel. 2. There are no statistically significant differences in the degree of benefit for GCSE students of lessons on the Syrian educational channel according to the variable of sex, while there are differences according to the variable of jurisdiction. 3. one of the most important reasons for students not to follow the channel is the magnitude of the curriculum, and electricity blackouts. On the impact of the findings, the researcher developed recommendations: 1 call for coordination between the education sector and the media sector in order to serve the educational process. 2 training courses for teachers to upgrade their competence regarding handling educational devices. 3. Greater attention to providing of facilities equipped to receive broadcast television for the lesson.